Using the UK standards for public involvement to evaluate the public involvement sections of annual reports from NIHR managed research centres - Alice Moult; Dereth Baker; Ali Aries; Paul Bailey; Steven Blackburn; Tom Kingstone; Saumu Lwembe; Zoe Paskins (Research Involvement and Engagement, 2023)
Abstract Background Within the United Kingdom (UK), the National Institute for Health and Care Research is the largest funder of health and social care research, and additionally funds research centres that support the development and delivery of research. Each year, award-holders of these research centres are required to write a report about their activities, including a summary of Patient and Public Involvement and Engagement (PPIE) activities. This study aimed to evaluate the PPIE sections of annual reports to identify best practice and challenges; this could inform future delivery of PPIE activities. Methods A framework documentary analysis informed by the six UK Standards for Public Involvement (‘Inclusive opportunities’, ‘Working together’, ‘Support and learning’, ‘Communications’, ‘Impact’ and ‘Governance’) was conducted on 112 reports. A quality improvement framework (‘Insights’) was used to evaluate quality as one of: ‘Welcoming’, ‘Listening’, ‘Learning’ and ‘Leading’. Recommendations from this review were co-developed with stakeholders and public contributors. Results Reports documented varying levels of quality in PPIE activities which spanned across all six UK Standards. Award-holders either intended to, or were actively working towards, increasing access and inclusivity of public involvement opportunities. Methods of working with public contributors were varied, including virtual and in-person meetings. Most award-holders offered PPIE support and learning opportunities for both public contributors and staff. Some award-holders invited public contributors to co-produce communication plans relating to study materials and research findings. The impact of public involvement was described in terms of benefits to public contributors themselves, and on an organisation and project level. Many award-holders reported inviting public contributors to share decision-making within and about governance structures. Conclusions This evaluation identified that most annual reports contained evidence of good quality PPIE practice with learning from public contributors. Using the UK Standards and Insights framework enabled exploration of the breadth and quality of PPIE activities. Recommendations include the need for a platform for centres to access and share PPIE best practice and for centres to collaborate with local and national partners to build relationships with the public through inclusive community engagement.